Social Sustainability in Europe. Pre- and Post-Pandemic Crisis - Gozzo, Simona; D’Agata, Rosario (SocietàMutamentoPolitica, 2024)
This paper aims to clarify the meaning and related dimensions of the concept of social sustainability, with reference to the Western European context. Social sustainability refers to the capacity to ensure fairness and equality, guaranteeing collective conditions of widespread well-being over time. Its outcomes being equity, empowerment, accessibility to public services, participation, sharing, cultural identity, and institutional stability. Changes of this magnitude are expected to have a significant impact on the social cohesion of each territory but also the potential attractiveness of the area. Given these premises, the work will use different (statistical) models of Bayesian networks built on European Social Survey data, distinguishing relationships between the selected indicators and describing the associated dynamics and processes. The goal is also showing importance of the context, considering the efficiency of European Social Model (ESM). Compare the pre- and post-pandemic Bayesian models is also one of the aims, so to detect conditions and political choices that might have shown resilience when facing a challenge such is a global emergency.